2010
DOI: 10.1007/s00401-010-0781-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients with IDH1 wild type anaplastic astrocytomas exhibit worse prognosis than IDH1-mutated glioblastomas, and IDH1 mutation status accounts for the unfavorable prognostic effect of higher age: implications for classification of gliomas

Abstract: provide evidence that the IDH1 status is more prognostic for overall survival than standard histological criteria that differentiate high-grade astrocytomas. We sequenced the isocitrate dehydrogenase 1 gene (IDH1) at codon 132 in 382 patients with anaplastic astrocytoma and glioblastoma from the NOA-04 trial and from a prospective translational cohort study of the German Glioma Network.Patients with anaplastic astrocytomas carried IDH1 mutations in 60%, and patients with glioblastomas in 7.2%. IDH1 was the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
522
3
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 738 publications
(571 citation statements)
references
References 25 publications
34
522
3
12
Order By: Relevance
“…Interestingly, the tumors in this latter group relatively infrequently showed copy number changes in EGFR, CDKN2A or PTEN, ie, markers reported to be indicative of aggressive biological behavior. Although IDH1 mutations are infrequently detected in glioblastomas from older patients (eg, in 8/144 older than 50 years (current study) or in 2 out of 126 glioblastoma patients older than 60 years, 17,34 these patients do not show a survival benefit, underlining once again that patient age in our study (450) should be considered when using molecular markers for assessment of prognosis. Knowing that IDH1 mutations are especially common in low-grade and anaplastic diffuse gliomas, in secondary glioblastomas and in younger patients, the lack of favorable prognostic meaning of IDH1 in the two groups just mentioned might be explained by assuming that molecular analysis was performed in these patients relatively late in their disease process.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, the tumors in this latter group relatively infrequently showed copy number changes in EGFR, CDKN2A or PTEN, ie, markers reported to be indicative of aggressive biological behavior. Although IDH1 mutations are infrequently detected in glioblastomas from older patients (eg, in 8/144 older than 50 years (current study) or in 2 out of 126 glioblastoma patients older than 60 years, 17,34 these patients do not show a survival benefit, underlining once again that patient age in our study (450) should be considered when using molecular markers for assessment of prognosis. Knowing that IDH1 mutations are especially common in low-grade and anaplastic diffuse gliomas, in secondary glioblastomas and in younger patients, the lack of favorable prognostic meaning of IDH1 in the two groups just mentioned might be explained by assuming that molecular analysis was performed in these patients relatively late in their disease process.…”
Section: Discussionmentioning
confidence: 57%
“…16 Furthermore, a recent study reported that glioblastomas carrying IDH1 mutations are associated with a better survival than anaplastic astrocytomas without these mutations. 17 Whether the recognition of an oligodendroglial component in glioblastomas has prognostic value is still under debate [18][19][20] and also within this glioblastoma subtype a different origin of this oligodendroglial component is hypothesized. 19 An age-dependent correlation-which was found for the prognostic effect of molecular markers like TP53, 1p loss and CDKN2A-may well contribute to the inconsistencies between studies on the prognostic relevance of specific molecular markers.…”
mentioning
confidence: 99%
“…Within the histological subtypes of GBMs, mutations in IDH1 are more common in secondary GBMs, fewer than 10% of primary cases and 70–80% of secondary GBMs harbored IDH1 mutations (Bleeker et al., 2012; Polivka et al., 2014; Takano et al., 2012; Thota et al., 2012) as well as in younger patients (Birner, Toumangelova‐Uzeir, Natchev, & Guentchev, 2011; Ducray et al., 2011; Hartmann et al., 2010; Juratli et al., 2012; Mellai et al., 2011). Our results are coherent with these data, 50% of secondary GBMs, and only 2.9% of primary GMBs carried IDH1 R132H mutation, however we do not find a significant relationship between mutation and younger patients (Table 3), showing a mean age of 52.6 years old in patients with IDH1 mutated and 51.8 years old in patients harboring the wild‐type allele.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is the most fatal primary brain cancer (Bleeker et al., 2012), and IDH1 mutations are frequent in the progressive pathway to secondary GBM (Thota et al., 2012). It is supposed that primary mutated GBMs, are, actually, secondary GBMs with no histological or radiological evidence in the evolution from a less malignant glioma (Bleeker et al., 2012; Hartmann et al., 2010). Several authors suggested that the mutation of IDH1 could occur in early stages of the glioma formation and could lead to tumor progression towards GBM (Juratli et al., 2012; Lewandowska et al., 2014; Thota et al., 2012; Weller et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation